Amyloid-like Prep1 peptides exhibit reversible blue-green-red fluorescence in vitro and in living cells. Issue 30 (17th March 2021) - Monti, Alessandra; Bruckmann, Chiara; Blasi, Francesco; Ruvo, Menotti; Vitagliano, Luigi; Doti, Nunzianna
Abstract : Florescence emission of the amyloid-like aggregates of the PREP1-based peptide in different contexts. The column of letters is the sequence of the peptide. Abstract : PREP1-based peptides form amyloid-like aggregates endowed with an intrinsic blue-green-red fluorescence with an unusual sharp maximum at 520 nm upon excitation with visible light under physiological conditions. The peptide PREP1[117-132], whose sequence does not contain aromatic residues, presents a pH-dependent and reversible fluorescence, in line with its structural transition from β-sheet rich aggregates to α-helix structures. These findings further demonstrate that the non-canonical fluorescence exhibited by amyloids is an articulated phenomenon.